Copper hexacyanoferrate as cathode material for hydrogen peroxide fuel cell. (25th September 2020) - Martins, R.F.; Martins, D.A.A.; Costa, L.A.C.; Matencio, T.; Paniago, R.M.; Montoro, L.A.
Abstract: The current need for handheld electronic devices with high energy autonomy has amplified research into clean and mobile energy source developments. Among suitable and promising technologies for this application, fuel cells, FCs are highlighted because of their minimal emission of pollutants and high efficiency. One type of FCs that has yet to be studied is the hydrogen peroxide/direct hydrogen peroxide fuel cell (DPPFCs). The present work is dedicated to the development of DPPFCs of one compartment using copper hexacyanoferrates (CuHCFs) as cathodic material and a Ni grid as anodic material. CuHCFs containing Fe II and/or Fe III were synthesized, characterized and their electrocatalyst performances were compared in 0.1 mol L −1 HCl and 0.5 mol L −1  H2 O2 . The maximum power densities reached for the CuFe II was 8.3 mW cm −2 and for the CuFe II Fe III was 2.9 mW cm −2 . The CuHCFs cathode materials show promising results, standing out as innovative materials for such an application. Highlights: Handheld electronic devices with high-energy autonomy. Clean and mobile energy source developments. One compartment Hydrogen peroxide/direct hydrogen peroxide fuel cell. Copper hexacyanoferrates as cathodic material and a Ni grid as anodic material. The maximum Fuel cell power density achieved was 8.3 mW cm −2 .